10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Takotsubo cardiomyopathy (TCM) can occur in young adults exposed to extreme physical stress, such as surgery, sepsis, and transfusion reactions. Mechanical recovery may precede electrical normalization, with ECG abnormalities persisting despite improved left ventricular ejection fraction (LVEF). Early recognition and monitoring are crucial to prevent misdiagnosis and guide management.